Synthesis of Oligosilanyl Compounds of Group 4 Metallocenes with the Oxidation State +3 - Arp, Henning (Organometallics, 2012)
Recently, we showed that titanocene silyls are much more stable with Ti in the oxidation state +3. The current study demonstrates that analogous Zr and Hf compounds can also be obtained by reaction of a suitable metalate precursor with an oligosilanyl dianion. As the obtained complexes formally possess a d(1) electron configuration, they were investigated using EPR spectroscopy. The corresponding spectra indicate that the compounds can be considered to also exhibit some cyclosilanyl radical anion character. In order to understand the strong preference of disilylated titan(IV)ocenes for reductive elimination, a theoretical study of the thermodynamics of these reactions was conducted, revealing that this behavior is essentially caused by the weak Si-Ti(IV) bond